Purification of Contaminated Water: Scientific and Islamic Analysis - Zia, Sana; Junaid Akbar, (Journal of Islamic and Religious Studies, 2018)
Water symbolizes life on the earth. All kinds of existence depend on water. Allah has created great reservoirs of water on this earth which cater to the needs of all living beings, but human negligence is making these resources polluted. Pollution not only poses threats to human life, it also endangers marine life and resources. These threats have been increased manifold by industrial revolution and increasing human population. The same factors are also responsible for the increased use of water. Many countries have employed distillation processes to provide clean water for the increasing demands of population, agriculture and industries. Islamic jurisprudence also takes into account different types of water, some of which can be used in cleansing rituals for worship, while some cannot be used. The question arises whether the purified water by scientific process will be "Ṭahir & Muṭṭahir" and can be used for ablution and other Islamic rituals? Will Islamic Jurist accept it as "Istiḥalah"? The following study will outline the details of distilled water to see whether it can be used for daily chores and ablution rituals or not.